EARLY MOBILIZATION AND THE ELASTIC BAND, AN EFFICIENT SOLUTION FOR AN INTUBATED SUBJECT: A CASE STUDY - Delia-Claudia STAN; Iosif SANDOR (Cluj University Press, 2023)
Introduction: In severely ill patients, weakness acquired in the intensive care unit is a frequent consequence. The advantages of early mobilization for adult intensive care unit patients include shorter stays in the intensive care unit and hospitals, a shorter need for mechanical ventilation, fewer days of harmful bedrest, fewer negative or dangerous occurrences, and increased walking distance. Early mobilization and rehabilitation programs using elastic bands for patients with severe illnesses in intensive care units enhance the weaning success and shorten ventilation times while also enhancing arm muscular power. Objective: This study case aimed to present the fact that early mobilization and elastic band exercises were efficient solutions for an intubated subject from the intensive care unit. Methods: A mechanically ventilated subject postoperatively for hiatal hernia and suspected phrenic nerve paresis, benefited from early mobilization and elastic band exercises and was assessed for the state of consciousness with the Richmond Agitation Scale, and muscle strength for the upper limb with the EH101 digital dynamometer. Results: Muscle strength at the level of the upper limbs increased from weak to normal and the subject was successfully extubated. Conclusions: In this case study we consider that early mobilization and the elastic band exercises program were effective, safe, inexpensive, and suitable for an intensive care unit, and it was the right solution for the success of weaning from the ventilator. REZUMAT. Mobilizarea precoce și banda elastică, o soluție eficientă pentru un subiect intubat: studiu de caz. Introducere: Slăbiciunea musculară dobândită în unitatea de terapie intensivă este o complicație frecventă la subiecții în stare critică. Beneficiile mobilizării precoce sunt: durata redusă în unitatea de terapie intensivă și a spitalizării, a ventilației mecanice, a zilelor de repaus la pat, efecte adverse minime și o distanță parcursă la mers mai mare. Mobilizarea  precoce și exercițiile cu banda elastică îmbunătățesc succesul extubării subiecților și reduc durata ventilației mecanice, de asemenea îmbunătățesc forța musculară la nivelul membrelor superioare. Obiective: Obiectivul acestui studiu de caz a fost, de a prezenta faptul că, mobilizarea precoce și exercițiile cu banda elastică au fost soluții eficiente pentru un subiect intubat din secția de terapie intensivă. Metode: Un subiect ventilat mecanic post-operator pentru hernie hiatală și suspect de pareza de nerv frenic a beneficiat de mobilizare precoce și exerciții cu banda elastică, fiind evaluat  pentru starea de conștientă cu Richmand Agitation Scale și forță musculară pentru membrele superioare cu dinamometrul digital EH101. Rezultate: Forța musculară la nivelul membrelor superioare a crescut de la nivel slab la normal iar subiectul a fost extubat cu succes. Concluzii: În acest studiu de caz considerăm că, mobilizarea precoce și programul de exerciții cu bandă elastică au fost eficiente, sigure, necostisitoare și potrivite pentru o unitate de terapie intensivă, si a fost soluția potrivită pentru succesul extubării subiectului. Cuvinte cheie: mobilizare precoce, bandă elastică, dinamometru digital, subiect ventilat, unitate de terapie intensivă. Received 2023 January 18; Revised 2023 June 15; Accepted 2023 June 16; Available online 2023 July 30; Available print 2023 August 30.